The Influence of Turmeric Powder (Curcuminoid) Levels in the Basal Diet on the Performance of Landrace Grower Phase Pigs - Djawapatty, David; Due, Maria Serviana; Kowe, Maria Stefania Goo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The prospects for pig farming in Bajawa are very promising, in line with the economic growth and the development of business centers that directly or indirectly support the increase in demand for pork. Several methods can be employed to improve the productivity of pigs in the grower-finisher phase, one of which is through feed improvement by providing alternative ingredients that can enhance nutrient utilization, such as turmeric powder (curcuminoid) as a feed additive. The purpose of this study is to examine the effects of turmeric powder (curcuminoid) supplementation at various levels in the basal diet on weight gain, feed intake, and feed conversion to determine the optimal level of turmeric powder supplementation in the basal diet and to analyze the economic benefits of using turmeric powder as a natural feed additive. The method of this research is an experimental method where there are 4 treatments and 3 replications between pigs given feed with turmeric powder and pigs given feed without turmeric powder. The variables observed include feed consumption, weight gain, and feed conversion. The level of turmeric powder addition in the basal diet affects the weight gain of pigs and the feed conversion value. Treatment R4 (85% feed and 15% turmeric powder) is the most optimal treatment. The research also shows a significant difference in the weight gain results of the pigs among each treatment, and there is a positive relationship between feed conversion and the weight gain of the pigs with a strong correlation category.